Two additions to the family Poaceae in the Flora of Allahabad District, Uttar Pradesh, India - Narain, Satya; Fatima, Nahid; Renu; Khare, Deepak; Sadhana (Current Botany, 2022)
A floristic exploration of the family Poaceae in Uttar Pradesh resulted in the addition of one Bamboo genus viz., Dendrocalamus strictus (Roxb.) Nees and one grass species viz., Chrysopogon aciculatus (Retz.) Trin. to the flora of Allahabad (U.P.). A detailed description, updated citation, phenology, habitat and distribution are provided which facilitates easy identification.